(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Power transformers are vital parts of electric energy transmission and generation systems. This article evaluates the causes of solid insulating dielectric degradation in power transformers based on operational stresses. Dissipation Factor (DF) or tan delta (Tan and power factor (PF) tests was conducted on the transformer windings based on the guard-to-ground-to-shield (GST) method using the Delta-3000 Megger instrument to measure winding capacitance (PF), leakage current, and Tan values. Findings revealed that there were large, sudden increases in variations in the winding capacitance values ranges from 2954 to 9638 and tan values from 0.9976 % to 1.241% measured after failure at 40 when compared to base value capacitance from 2569 to 8381 and tan values from 0.344 % to 0.428% measured at 30 before transformer failure. These higher changes in tan overtime, capacitance (PF), and leakage current indicated deteriorating insulating material conditions, contaminations, dielectric losses and degradation. Also, thermal stress caused mechanical deterioration with time at an elevated temperature and degradation; Mechanical stress caused transient currents during switching on power transformer, damaged insulation due to mechanical vibration; Electrical stresses create significant high-voltage exposure to voltage transients; and Environmental stresses results due to presence of moisture, dirt, chemicals, radiation, or other contaminants. The proposed Condition monitoring can be used to monitor transformers parameters such as dissolving gas analysis, partial discharge, oil quality, vibration, moisture, windings temperatures, detect faults at incipient stage; avoid catastrophic events; Optimized maintenance and prevent failures.